Apoyo social y síntomas de depresión postparto en puérperas en la ciudad de Riohacha (2024)
The aim of this research is to analyze the relationship between social support and postpartum depression symptoms in breastfeeding women from Riohacha. Considering postpartum depression as a national issue that particularly affects mothers with little social support, this study seeks to provide a deeper understanding of this phenomenon. The research question posed is: What is the relationship between social support and postpartum depression symptoms in postpartum women from Riohacha? The theoretical framework addresses the Adult Life Cycle, highlighting that, in adulthood, social support plays a crucial role in emotional and physical well-being, especially during pregnancy and the postpartum period. Theoretical models such as those by House and Kahn, Cohen and Wills, and Uchino are explored, examining different dimensions and effects of social support.